Spatiotemporal dynamics of human leptospirosis and its relationship with rainfall anomalies in Colombia (2018)
Background In Colombia, human leptospirosis (HL) is a disease that has had a mandatory notification rule since 2007. Humans usually acquire the infection through water contaminated with animal urine that comes into direct contact with cutaneous lesions, eyes or mucous membranes. Objectives To analyze the spatiotemporal variability in the occurrence of HL cases in Colombia between 2007 and 2016, and its relation with the El Niño Southern Oscillation (ENSO) cycle and the consequent anomalies in rainfall in spatiotemporal clusters. Methods An ecological study of the HL cases, aggregated by municipality, and reported between 2007 and 2016, is presented. Findings During the period of study, 9928 cases of HL were reported, and 58.9% of the municipalities reported at least one case of leptospirosis. Six spatiotemporal clusters were identified—five were in the Andean region and one was in the Caribbean region. The assessment of the ENSO cycle and rainfall anomalies suggests the importance of La Niña episodes, and excess rainfall periods in the occurrence of cases of HL. Conclusions Our results demonstrate the importance of the ENSO cycle, rainfall periods and periods with excess rainfall in the occurrence of cases and outbreaks of HL in Colombia, and suggest the importance of the topography of valleys and flood zones as zones in which the risk of infection is elevated.